Clinical, pathologic, and toxicologic characterization of Salvia reflexa (lance-leaf sage) poisoning in cattle fed contaminated hay. (May 2021) - Panter, Kip E.; Stegelmeier, Bryan L.; Gardner, Dale R.; Stonecipher, Clinton A.; Lee, Stephen T.; Kitchen, Don; Brackett, Adeline; Davis, Charlie
Salvia reflexa (lance-leaf sage)-contaminated alfalfa hay was fed to 500 mixed-breed beef cattle. Within hours of exposure, nearly half of the cattle developed lethargy, anorexia, depression, and recumbency, followed by bellowing, colic, and death. Even though the uneaten contaminated hay was removed the first day, nearly 100 animals died within the first 48 h. Three of these cattle were examined postmortem, and tissues and hay samples were collected for microscopic and chemical analysis. Several days later, a smaller number of the clinically poisoned cattle developed neurologic disease with aberrant behavior, aggression, icterus, blindness, exhaustion, and death. A total of 165 cattle were fatally poisoned. Poisoned cattle had swollen, dark, mottled livers that had a prominent nutmeg-like lobular pattern on cut section. Histologically, there was severe centrilobular-to-panlobular hepatic necrosis with marked hepatocellular swelling, degeneration, and necrosis. The surviving cattle developed liver disease characterized by altered serum biochemical analyses and microscopic hepatocellular degeneration and necrosis. In subsequent biopsies and analysis, these lesions resolved within 6–7 mo. After confirming toxicity of the hay in cattle, goats, and mice, followed by a mouse bioassay–guided chemical fractionation process, Salvia reflexa was identified as the contaminant in the hay responsible for the hepatotoxicity. S. reflexa has not been reported previously to cause fatal hepatotoxicity in livestock in North America, to our knowledge.